2008
DOI: 10.1080/00140130802376026
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in foot shape

Abstract: The purpose of the study was to investigate sex-related differences in foot morphology. In total, 847 subjects were scanned using a 3-D-footscanner. Three different analysis methods were used: (1) comparisons were made for absolute foot measures within 250-270 mm foot length (FL); (2) and for averaged measures (% FL) across all sizes; (3) the feet were then classified using a cluster analysis. Within 250-270 mm FL, male feet were wider and higher (mean differences (MD) 1.3-5.9 mm). No relevant sex-related diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 26 publications
4
60
1
3
Order By: Relevance
“…The present finding is in contrast with Abledu et al(2015), Krauss et al(2008), Wunderlich et al(2001), Krishan and Sharma (2007), Krishan et al(2012), Fessler et al(2005), Kanchan et al(2008), Agnihotri et al(2007aAgnihotri et al( , 2007b where all the footprint dimensions were significantly greater in boys than girls. However, this study is in consistent with Hernandez et al 2006 where SPAI showed no significant difference in terms of gender.…”
Section: Discussioncontrasting
confidence: 57%
“…The present finding is in contrast with Abledu et al(2015), Krauss et al(2008), Wunderlich et al(2001), Krishan and Sharma (2007), Krishan et al(2012), Fessler et al(2005), Kanchan et al(2008), Agnihotri et al(2007aAgnihotri et al( , 2007b where all the footprint dimensions were significantly greater in boys than girls. However, this study is in consistent with Hernandez et al 2006 where SPAI showed no significant difference in terms of gender.…”
Section: Discussioncontrasting
confidence: 57%
“…They cover a wide spectrum of different topics relevant for shoe production, medicinal and forensic research: age estimation (Hackman et al, 2013), sexual dimorphism and sex determination (Fessler et al, 2005;Atamturk, 2010;Krauss et al, 2011aKrauss et al, , 2011bKautilya et al, 2013;Kanchan et al, 2014;Keme Ebimobo et al, 2014;Rahman et al, 2014), body size estimation (Mohanty et al, 2012), and uniqueness (see Bennett and Morse, 2014, pp. 180ff) as well as anthropological basics (growth of foot) (Davenport, 1932;Meredith, 1944;Anderson et al, 1956;Mauch et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of this exclusion are papers by Bradshaw and Rossignol, [32], De Paula et al [33] and Ibrahim et al [34]. Studies that presented 3D or photography methods (2D) to collected data were also excluded [35,36]. Several studies were not considered in this review because the sample considered comprised only university students [37] or only male workers [38], instead of younger school students.…”
Section: Methodsmentioning
confidence: 99%